2007
DOI: 10.1590/s0100-40422007000200016
|View full text |Cite
|
Sign up to set email alerts
|

Pré-concentração de cádmio com Saccharomyces cerevisiae e determinação em águas fluviais usando espectrometria de emissão óptica com plasma indutivamente acoplado

Abstract: Recebido em 7/12/05; aceito em 16/5/06; publicado na web em 26/9/06 PRECONCENTRATION OF CADMIUM WITH Saccharomyces cerevisiae AND DETERMINATION IN RIVER WATER USING INDUCTIVELY COUPLED PLASMA OPTICAL EMISSION SPECTROMETRY. A preconcentration method based on the use of Saccharomyces cerevisiae as sorbent material is proposed for the determination of Cd(II) in river water. The solid phase extraction was performed in batch mode and the determination of the analyte in the solid phase was easily carried out by intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One possible explanation is that this species could be a bioaccumulator of metals, or also that its cell wall can act as a good adsorbent for these elements (Bishnoi and Garima, 2005), therefore more studies on the interaction between these elements and these microorganisms would be needed. Previous studies have demonstrated the possibility of using other genera of yeasts, such as Saccharomyces cerevisiae, as sorbent material capable of removing metal ions such as Cd (II) from river water (Biscaro et al, 2007;Meneg ario et al, 2010) and bioaccumulation of Cu(II) by Pichia guilliermondii (teleomorph Meyerozyma guilliermondii) (De Sil oniz et al, 2002;Meneg ario et al, 2007), which may explain the decrease in the solubilization of this metal in the co-inoculation assays (Fig. 3).…”
Section: Concentrations Of Metals During the Bioleaching Processmentioning
confidence: 99%
“…One possible explanation is that this species could be a bioaccumulator of metals, or also that its cell wall can act as a good adsorbent for these elements (Bishnoi and Garima, 2005), therefore more studies on the interaction between these elements and these microorganisms would be needed. Previous studies have demonstrated the possibility of using other genera of yeasts, such as Saccharomyces cerevisiae, as sorbent material capable of removing metal ions such as Cd (II) from river water (Biscaro et al, 2007;Meneg ario et al, 2010) and bioaccumulation of Cu(II) by Pichia guilliermondii (teleomorph Meyerozyma guilliermondii) (De Sil oniz et al, 2002;Meneg ario et al, 2007), which may explain the decrease in the solubilization of this metal in the co-inoculation assays (Fig. 3).…”
Section: Concentrations Of Metals During the Bioleaching Processmentioning
confidence: 99%
“…The imprinted IPN had higher adsorption capacity and exhibited superior reusability and stability. The Brazilian group, Biacaro et al 58 chose to preconcentrate Cd on baker's yeast, Saccharomyces cerevisiae for the determination of Cd II in river water. The same group, with Menegario as the primary author, 35 also investigated the adsorption of Cd-metallothioneins from biological abstracts.…”
Section: Preconcentrationmentioning
confidence: 99%
“…8,9 Because of these problems, a separation and preconcentration process is necessary for improving the sensitivity of the analytical detection method and for providing low detection limits. Various separation/preconcentration techniques, including solid phase extraction (SPE), 10,11 ion exchange, 12 cloud point extraction, 13 membrane filtration, 14 electroanalytical techniques, 15 and coprecipitation, 16 are used prior to instrumental determination of trace elements. SPE is the most widely used preconcentration technique for the determination of trace elements.…”
Section: Introductionmentioning
confidence: 99%